2021
DOI: 10.1021/acs.orglett.1c03098
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Chromium Catalysts by Photoexcited Hantzsch Ester for Decarboxylative Allylation of Aldehydes with Butadiene

Abstract: Metallaphotocatalysis often needs light-absorbing metal-polypyridyl complexes, semiconductors, or organic dyes, which can modify the oxidation state of metal catalysts. Here, we first report that photoexcitation of Hantzsch ester can directly activate chromium reagents through a single-electron transfer process. The synthetic application was demonstrated through a photoredox decarboxylative allylation of aldehydes with feedstock butadiene without exogenous photocatalysts, metallic reductants, or additives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 37 publications
1
17
0
Order By: Relevance
“…Complementing this example, Shi and co-workers reported the decarboxylative allylation of aldehydes with butadiene through the photoexcitation of Hantzsch esters, obviating the need for exogenous photocatalysts. 48 Alongside our work, a number of related allylations of carbonyl compounds involving radicals enabled by dual catalysis have also been developed. 49−51 The Shi group devised an excellent three-component allylation of carbonyls with 1,3-butadiene by dual photoredox/Ti catalysis.…”
Section: Catalytic Generation Of Allylic Chromium Intermediatesmentioning
confidence: 99%
“…Complementing this example, Shi and co-workers reported the decarboxylative allylation of aldehydes with butadiene through the photoexcitation of Hantzsch esters, obviating the need for exogenous photocatalysts. 48 Alongside our work, a number of related allylations of carbonyl compounds involving radicals enabled by dual catalysis have also been developed. 49−51 The Shi group devised an excellent three-component allylation of carbonyls with 1,3-butadiene by dual photoredox/Ti catalysis.…”
Section: Catalytic Generation Of Allylic Chromium Intermediatesmentioning
confidence: 99%
“…Recently, Hao and Shi reported a similar catalytic threecomponent coupling of aldehydes 1, 1,3-diene 24, and NHPI ester 32 (Scheme 10). 44 They utilized Hantzsch ester (HE) as a photoactive reductant for the chromium catalyst. 45 Considering the reduction potential of the excited state of HE [E 1/2 (HE •+ /HE*) = -2.28 V vs SCE], 45 chromium(III) species was reduced by HE* [E 1/2 (Cr(III)/Cr(II)) = -0.41 V vs SCE].…”
Section: Short Review Synthesismentioning
confidence: 99%
“…29,30 Inspired by these achievements, we hope to harness the reduction potential of HE* for chromium catalysis. 31 Herein, we report the first photochemical NHK coupling of alkenyl triflates and aldehydes enabled by photoexcited HE* (Figure 1c).…”
mentioning
confidence: 92%
“…Very recently, utilization of photoexcited HE* as a potential photoreductant (−2.28 V versus SCE) for metallaphotoredox catalysis appealed to great interests. Melchiorre and Molander respectively reported that photoexcited HE* and its analogs can reduce Ni to low valence catalytically active species for C–C bond coupling. , Inspired by these achievements, we hope to harness the reduction potential of HE* for chromium catalysis . Herein, we report the first photochemical NHK coupling of alkenyl triflates and aldehydes enabled by photoexcited HE* (Figure c).…”
mentioning
confidence: 93%